Energizing Intention to Visit Rural Destinations: How Social Media Disposition and Social Media Use Boost Tourism Through Information Publicity - Shang, Yunfeng; Mehmood, Khalid; Iftikhar, Yaser; Aziz, Atif; Tao, Xuedan; Shi, Liting (Frontiers in Psychology, 2021)
The purpose of this study is to examine the impact of information publicity on tourists’ intention to visit rural destinations in developing countries. Based on the theory of planned behavior (TPB), we examine the indirect effect of information publicity on intention to visit via subjective norms and further investigate the moderating effect of social media disposition and social media use. The study using data from a time-lagged design with three waves supports the hypothesized model. The findings reveal that information publicity influences tourists’ intention to visit through the mediating effect of subjective norms. Also, the social media disposition strengthens the relationship between information publicity and subjective norms. Furthermore, social media use positively moderates the relationship between subjective norms and intention to visit. Besides the core TPB constructs, the added variables indeed exert a substantial impact on tourists’ visit intention. The study contributes to the tourism-related literature on social media and the practical implications are discussed.